Beta-blocker use and acute exacerbations of COPD following myocardial infarction: a Danish nationwide cohort study. Issue 11 (20th August 2020) - Rasmussen, Daniel B; Bodtger, Uffe; Lamberts, Morten; Torp-Pedersen, Christian; Gislason, Gunnar; Lange, Peter; Jensen, Magnus T
Abstract : Introduction: Patients with chronic obstructive pulmonary disease (COPD) are undertreated with beta-blockers following myocardial infarction (MI), possibly due to fear for acute exacerbations of COPD (AECOPD). Is beta-blocker use associated with increased risk of AECOPD in patients following first-time MI? Methods: Danish nationwide study of patients with COPD following hospitalisation for MI from 2003 to 2015. Multivariable, time-dependent Cox regression accounting for varying beta-blocker use based on claimed prescriptions during up to 13 years of follow-up. Results: A total of 10 884 patients with COPD were discharged after first-time MI. The 1-year rate of AECOPD was 35%, and 65% used beta-blockers at 1 year. Beta-blocker use was associated with a lower risk of AECOPD (multivariable-adjusted HR 0.78, 95% CI 0.74–0.83). This association was independent of the type of MI (HR 0.70, 95% CI 0.59–0.83 in ST-elevation MI (STEMI) and HR 0.80, 95% CI 0.75–0.84 in non-STEMI), presence or absence of heart failure (HR 0.82, 95% CI 0.74–0.90 and HR 0.77, 95% CI 0.72–0.82, respectively), beta-blocker dosage and type, as well as exacerbation severity. Results were similar in 1118 patients with full data on COPD severity and symptom burden (median forced expiratory volume in 1 s as percentage of predicted was 46 and majority had moderate dyspnoea), and in 1358 patients with severe COPD and frequent AECOPD with a high 1-year rate of AECOPD of 70%. Discussion: Beta-blocker use was not associated with increased risk of AECOPD following MI. This finding was independent of COPD severity, symptom burden and exacerbation history, and supports the safety of beta-blockers in patients with COPD, including high-risk patients with severe disease.